¿Hacia dónde se mueven los desempleados en Venezuela? (2017)
According to official figures in Venezuela both unemployment and GDP show a decreasing trend, which leads one to wonder what explains this contradiction. The fall of unemployment in the midst of a period of economic recession is only possible if individuals undertake informal activities that distance them from unemployment without reporting their activity, or if they leave the job search in the face of the impossibility of finding work. Based on the Household Survey by Sampling for 2012 and 2013, this study analyzes the average duration of unemployment and the destination of the unemployed, using Markovian transition matrices. The results show an incidence of long-term unemployment of more than 40 %, which induces some individuals to opt for either of these two alternatives.